2020
DOI: 10.1515/chem-2020-0070
|View full text |Cite
|
Sign up to set email alerts
|

A study on the bacterial adhesion of Streptococcus mutans in various dental ceramics: In vitro study

Abstract: Streptococcus mutans (S. mutans) has been identified as a major etiologic agent of human dental caries and forms a significant proportion of oral streptococci in carious lesions. This study investigates the correlation of surface properties (effect of contact angle [CA] and free surface energy) on three restorative materials (zirconia, nickel–chromium–molybdenum alloy and composites) used in dental prosthetics with bacterial adhesion to S. mutans. Ten samples of each material (zirconia, nickel–chromium–molybde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…An increase in SFE usually results in increased adhesion of bacteria. 43,44 The application of BOA resulted in a slight (by $1 mN/m) increase in SFE and a significant ($ 78%) reduction in the number of adhered bacterial cells. This indicated that BOA affected bacteria directly by the contact-killing mechanism and not passively via changes in thermodynamic properties and reduced adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in SFE usually results in increased adhesion of bacteria. 43,44 The application of BOA resulted in a slight (by $1 mN/m) increase in SFE and a significant ($ 78%) reduction in the number of adhered bacterial cells. This indicated that BOA affected bacteria directly by the contact-killing mechanism and not passively via changes in thermodynamic properties and reduced adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported before that the adhesion of bacteria is related to surface free energy. An increase in SFE usually results in increased adhesion of bacteria 43,44 . The application of BOA resulted in a slight (by ~1 mN/m) increase in SFE and a significant (~ 78%) reduction in the number of adhered bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 13) reported that the potential of gold alloys with higher surface energies facilitated greater adhesion of early colonized bacteria (S. oralis, S. sanguinis, and S. gordonii) compared to that on zirconia, alumina-toughened zirconia, and titanium surfaces. Bislimi et al 32) found that the surface energies of different materials (zirconia, metal alloys, and CRs) correlated with their susceptibility to S. mutans adhesion. The surface energy is also affected by the surface roughness.…”
Section: Mutans (E)mentioning
confidence: 99%